Характеристика екскреції катехоламінів із добовою сечею у дітей дошкльного віку з депривацією - Пеньков, А. Ю.; Макєєва, Н. І.; Ріга, О. О. (Clinical Endocrinology and Endocrine Surgery, 2014)
The results of general metanephrines, epinephrine, norepinephrine daily urine levels in children of preschool age depending on environment (stay in orphan institutions, stay in foster families, parent’s family) were investigated and had presented at this article. The differences of catecholamine’s urine excretion and theirs medium metabolites have been detected. There was elevation of general metanephrine and epinephrine and depression of norepinephrine excretion in orphans.